(untitled) (Conferencea, 2022)
The purpose of this article is to explain the concepts and differences between diplomatic and consular immunity, the circumstances under which diplomatic immunity arises, the privileges of employees of diplomatic missions and consular posts, and their liability in the event of a crime.